Psychological Distress in the COVID-19 Patients and their Family Members of Makawanpur District, Nepal - Dhital, Krishna Prasad; Karki, Tej Bahadur; Nepali, Karna (International Research Journal of MMC, 2021)
The prevalence of COVID-19 and its effect was spread all over the worldwide. Nepal also suffered bitterly from the effect of COVID-19. The main objective of this study is to identify the psychological distress in the COVID-19 patients and their family members living in Makawapur Gadhi Rural Municipality of Makawanpur district. The data was collected from 30 households who were suffering from the infection of COVID-19. The result shows that 26.7% of the respondents felt no distress, while 60% respondents felt moderate distress and 13.3% respondents felt severe distress from pandemic of COVID-19. From the statistical analysis, there was no significant effect of demographic variables (Gender, Caste, Age, Education, Employment Status, and Patients types) on level of distress. There is need to provide the socio-psychological counselling to the COVID-19 patients and family members to manage their distress.